2023
DOI: 10.5194/nhess-2023-228
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Text-mining uncovers the unique dynamics of socio-economic impacts during multi-year drought

Jan Sodoge,
Christian Kuhlicke,
Miguel D. Mahecha
et al.

Abstract: Abstract. Droughts often lead to cross-sectoral and interconnected socio-economic impacts, affecting human well-being, ecosystems, and economic development. During extended drought periods, such as the 2018–2022 event in Germany, these impacts are amplified due to temporal carry-over effects. Yet, our understanding of drought impact dynamics during increasingly frequent multi-year drought periods is still in its infancy. In this study, we analyze the socio-economic impacts of the 2018–2022 multi-year drought i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…FDs are becoming increasingly frequent under climate change, and require different adaptation schemes owing to their rapid emergence (Yuan et al 2023;Christian, Hobbins, et al 2024). In this regard, we investigated the occurrence of FDs in Germany, as well as societal awareness (Kam, Stowers, and S. Kim 2019) and perceived impacts (Sodoge et al 2023). Using these digital trace data, our study shows the delayed response of social perception to FDs as reported in the media and according to online search behavior.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…FDs are becoming increasingly frequent under climate change, and require different adaptation schemes owing to their rapid emergence (Yuan et al 2023;Christian, Hobbins, et al 2024). In this regard, we investigated the occurrence of FDs in Germany, as well as societal awareness (Kam, Stowers, and S. Kim 2019) and perceived impacts (Sodoge et al 2023). Using these digital trace data, our study shows the delayed response of social perception to FDs as reported in the media and according to online search behavior.…”
Section: Discussionmentioning
confidence: 98%
“…Socio-economic impact data To assess the perceived impacts of flash droughts on different socio-economic sectors, we used information on reported socio-economic impacts in newspaper articles. Specifically, we used the approach and data by Sodoge et al (2023), which consider the frequency of newspaper articles reporting on a specific drought impact using text-mining tools. Therefore, we examined approximately 50,000 newspaper articles that included terms related to conventional drought (e.g.…”
Section: Trend Analysismentioning
confidence: 99%
See 3 more Smart Citations